2015
DOI: 10.1042/bst20140311
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TRPML1 function

Abstract: TRPML1 is a ubiquitously expressed cation channel found on lysosomes and late endosomes. Mutations in TRPML1 cause mucolipidosis type IV and it has been implicated in Alzheimer's disease and HIV. However, the mechanisms by which TRPML1 activity is regulated are not well understood. This review summarizes the current understanding of TRPML1 activation and regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…Trehalosemediated nuclear translocation of TFEB and autophagy activation in macrophages was also recently implicated as a potential therapy for atherosclerosis [52]. Activation of the MCOLN1 channel is dependent on its interaction with PtdIns (3,5)P2, a product of the enzymatic action of PIKFYVE [39,53]. The role of PIKFYVE in regulating autophagy in itself is debatable, with literature references supporting both proand anti-autophagy properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trehalosemediated nuclear translocation of TFEB and autophagy activation in macrophages was also recently implicated as a potential therapy for atherosclerosis [52]. Activation of the MCOLN1 channel is dependent on its interaction with PtdIns (3,5)P2, a product of the enzymatic action of PIKFYVE [39,53]. The role of PIKFYVE in regulating autophagy in itself is debatable, with literature references supporting both proand anti-autophagy properties.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PIKFYVE in regulating autophagy in itself is debatable, with literature references supporting both proand anti-autophagy properties. Thus, while PIKFYVE through PtdIns(3,5)P2 can activate MCOLN1 [39,53], it is also reported that both PtdIns(3,5)P2, as well as PndIns5P, can activate MTOR pathway, which should negatively regulate autophagy [54,55]. In fact, PtdIns(3,5)P2 serves as the precursor for entire cellular PtdIns5P content, most likely through some phosphatase activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…274 ), and displayed an additive effect in combination with the endogenous activator phospha tidylinositol3,5bisphosphate (PtdIns(3,5)P2) 274,303 . An analogue of SF22, in which chlorine on the thiophene had been replaced by a methyl group, showed greater efficacy on TRPML1 activation 303,304 . Another molecule called ML SA1 (FigS 2,3), acting as a mucolipin synthetic agonist, also showed an additive effect with endogenous PtdIns(3,5)P2 on TRPML1 channels 305 .…”
Section: V-atpase Inhibitorsmentioning
confidence: 99%
“…They are likely filled by Ca 2+ -H + exchange (Melchionda et al, 2016) and express members of the transient receptor potential mucolipin (TRPML) and two-pore channel (TPC) families to effect Ca 2+ release (Grimm et al, 2012; Kiselyov et al, 2012; Patel, 2015; Waller-Evans and Lloyd-Evans, 2015). Three TRPML isoforms are present in humans (García-Añoveros and Wiwatpanit, 2014).…”
Section: Introductionmentioning
confidence: 99%